Are genetically distinct lizard species able to hybridize? A review. Issue 1 (1st February 2015) - Jančúchová-Lásková, Jitka; Landová, Eva; Frynta, Daniel
Abstract: Animal species are delimited by reproductive isolation mechanisms (RIMs). Postzygotic RIMs are mainly products of genetic differences and thus their strength increases with elapsed divergence time. The relationship between postzygotic reproductive isolation and genetic divergence, however, differs considerably among major clades of vertebrates. We reviewed the available literature providing empirical evidence of natural and/or experimental hybridization between distinct species of lizards (squamates except snakes). We found that hybridization events are widely distributed among nearly all major lizard clades. The majority of research focuses on parthenogenetic species and/or polyploid hybrids in families Lacertidae, Teiidae and Gekkonidae. Homoploid bisexual hybrids are mainly reported within Lacertidae and Iguania groups. As a proxy of genetic divergence of the hybridizing taxa we adopted nucleotide sequence distance (HKY85) of mitochondrial cyt b gene. The upper limit of genetic divergence was similar with regard to both parthenogenetic and bisexual hybrids. Maximum values of these distances between hybridizing species of lizards approached 18%?21%, which is comparable to or even exceeds the corresponding values reported for other principal clades of vertebrates. In spite of this, F1 hybrids are typically at least partially fertile in lizards and thus genetic in-trogression between highly divergent species is possible. The relationship between the genetic distance and hybrid fertility was not found.